(untitled) (Fenestella. Inside Medieval Art, 2022)
This article reconsiders some aspects of the early medieval monastic settlement of Torba, starting from an established historiography and the very recent publication of new archaeological data. Focusing on the Monastery tower, which had been part of the late antique curtain wall of Castelseprio, the research has led to a new interpretation of the construction phases and functions. The contribution thus offers new hypotheses for interdisciplinary evaluation, particularly about the possibility that the monastic choir might have been installed in a space not consecrated. The mural paintings of both the tower and the church of Santa Maria remain to be reconsidered in detail, as well as the relationship with the monastic building leaning against the curtain wall. The results should later be compared with the updated research on female monastic settlements in the early medieval West.